Gulqand: A Nutraceutical from Sugared Petals - Forough Afsari Sardari; Amir Azadi; Abdolali Mohagheghzadeh; Parmis Badr (Tehran University of Medical Sciences, 2018)
Edible flowers have traditionally been used in various foods and beverages. Besides their usage in culinary arts for flavor and garnish, they are known as nutraceuticals because of having phytochemicals and biological properties. Based on Traditional Persian Medicine, Gulqand is a two-ingredient dosage form containing one type of edible petal mixed with sugar. The most famous Gulqand is prepared with Rosa damascena flowers. In current study, keyword of Gulqand was searched in three medieval Persian manuscripts. Different formulations, preparation method, temperament, effects, multi-ingredient formulations which contain Gulqand, and their applications were extracted. Most of side effects which can be controlled by R. damascena Gulqand was gastrointestinal or relevant to central nervous system like flatus and headache. Golqands, the traditional nutraceutical from sugared petals, are potentials for further research and new products.